Critical Study of Juvenile Justice System in Pakistan - Fayyaz, Aamir (Journal of Pakistan Administration, 2021)
Humans, being social animals, love to live with others of their kind. Society and the State join hands to provide them with an opportunity to live in an organized way and complement each other in relationships of diverse nature. The social contract defines this relationship and is meant to subject the members of society to some form of broader institutional controls so as to allow each individual progress in his or her life and strive for self-actualization in diverse manner. The contract tends to evolve with time and at any point of time remains fluid and susceptible to change in order to adjust the variations in the value system and to define and re-define, on continuous basis, human life in the society. It is interesting to note how this rather abstract contract affects the very existence of humans, made of flesh and blood. That explains to some extent, how and why, despite its overarching presence, balancing the collective state-societal expectations and an individual’s desires and needs remains a challenge.
Keywords: Juvenile Justice System; Pakistan; self-actualization; contract tends; society